Letter (translation) - Carrillo, Wenceslao
026-0047-001 TRANSLATION. London, 10th July, 1939. Comrade L. Evans. I have your letter of 7th instant, reference CON.LE.JSJ, and the enclosed copy of "Labour" which you were good enough to send. The problem of my children has taken a different turn from what it has been hitherto, and one which is very distressing. My son, José Luis, the aircraft engineer, has written to me saying that he has now got everything arranged to go to Russia. My daughter Blanca and her husband have also applied for permission to go to that country. All I now have left are the two youngest, Nora and Roberto, whom I wish to bring to England, instead of leaving them at Oran. In addition, certain political matters have been developing in London for some time now, relating to Spain, which interest me, and which I am concerned to follow with great apprehension and to be fully informed about. These political matters relate to Spaniards and Englishmen, and revolve around Colonel Casado and the National Council of Defence. We have met in London the five members of this body whom we saved from Fascism, and I am the sole representative of the Socialist Party on the Council. If you would like to have a talk on this point, please tell me the time and day on which you would be able to receive me, and I will ask Comrade Araquistain to accompany me to act as interpreter. Will you urge the friends at the T.U.C. to see if it is not possible to bring my two children, Nora and Roberto, to England? I hope to hear from you. I shall not go away until I know definitely whether or not you can get my children over here. Please take into account the domestic situation with which I am faced by my children going to Russia and the political situation which advises me to remain here. Yours sincerely, (signed) W. Carrillo. AC. 292/946/26/47